IMPLEMENTATION OF ORGANIZATIONAL COMMUNICATION STRATEGIES IN IMPROVING EMPLOYEE PERFORMANCE - Angelina Purnama,; Anisti,; Tuty Mutiah, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Organizational communication plays a crucial role in determining employee performance effectiveness, especially amid the dynamic challenges of the modern workplace. PT Alton Yogantara Perkasa, a company engaged in construction services, faces the need to continuously enhance employee productivity and efficiency. This study aims to analyze the organizational communication strategies implemented to improve employee performance. The research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews with management and employees, and internal company documentation. The results indicate that effective communication strategies such as two-way communication, information transparency, and regular feedback delivery create a conducive work environment and enhance employee motivation. Moreover, the use of internal digital communication media accelerates information flow and strengthens interdepartmental coordination. Participatory communication also reinforces employees’ sense of involvement and responsibility toward achieving organizational goals. Therefore, well-planned, adaptive, and participatory communication strategies play a significant role in supporting the sustainable improvement of employee performance at PT Alton Yogantara Perkasa.